Pengaruh Profitabilitas, Aktivitas, dan Arus Kas Operasi terhadap Financial Distress pada Perusahaan Sektor Teknologi yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2020-2024 - Inka Bunga Hasanah; Santi Deswita (Lembaga Yasin AlSys, 2026)
Although financial distress among technology-sector companies has been widely studied as an early indicator of potential bankruptcy, research specifically analyzing the effects of profitability, activity, and operating cash flow on financial distress among technology-sector companies listed on the Bursa Efek Indonesia (BEI) during the 2020–2024 period remains limited. This study aims to analyze the effects of profitability, activity, and operating cash flow on financial distress. This study employed a quantitative approach with a causal design and utilized secondary data in the form of companies’ annual financial statements. The sample was determined through purposive sampling based on specific criteria for technology-sector companies listed on the BEI during the 2020–2024 period. Data were collected using the documentation method and analyzed through multiple linear regression with the assistance of IBM SPSS, including descriptive statistics, classical assumption tests, partial tests (t-test), simultaneous tests (F-test), and the coefficient of determination (R²). The results showed that profitability, activity, and operating cash flow played a role in explaining companies’ financial distress conditions. Companies with low profitability, declining asset-use effectiveness, and weak operating cash flow tended to have a higher risk of financial distress. These findings strengthen the application of agency theory and signaling theory in explaining the relationship between financial performance and potential financial difficulties. This study contributes to the development of financial distress prediction research and provides practical implications for company management, investors, and creditors in detecting potential financial difficulties as a basis for decision-making. Future studies are recommended to expand the research objects, observation periods, and variables to obtain more comprehensive results.